Maize residue management in Myanmar - Myanmar Agrifood Program for Strategy and Analysis (International Food Policy Research Institute, 2024)
This note provides an overview of maize residue management practices in Myanmar based on interviews conducted in June 2024 with a sample of 599 maize farmers in the primary maize growing region. Key Findings  Burning maize residues is not the most common practice in Myanmar, and the share of farmers burning fell from 44 percent in 2013 to 34 percent in 2023 as farmers have adopted alternate approaches, such as retaining residues in the soil.  The broader maize sector evolution over the last decade has brought several changes, some of which likely increase the relative benefits of burning – e.g., decline in labor availability, decline in livestock ownership.  Access to markets for maize residues has improved, though still less than one fifth of farmers can sell their maize residues.  Soil fertility is important to farmers. Soil fertility improvement was the most common reported benefit to both burning and retaining residues. However, most farmers that do not burn disagree that soils are improved by burning, while most farmers that burn agree.  Most farmers are aware of the human health effects of burning, but more than a quarter strongly disagree that burning residues negatively affects the health of others.  The majority of farmers that burn agree that their community expects them to. Recommendations  Farmer education and extension are leading candidates to reduce maize residue burning in Myanmar. Key topics where there are evident knowledge gaps include highlighting the large relative gains in long-term soil health from retaining the residues compared to burning, and the high external health costs of burning.  Interventions to reduce burning are critical to reducing environmental and health externalities, and in light of the planned Thai bans in the importation of maize from countries using burning as a residue management practice. However, the Thai government should adapt their strategy and consider other methods to reduce residue burning in neighboring countries including supporting education, or providing price incentives or reduced tariffs for not burning as opposed to outright bans which would likely have limited effects on burning decisions at the farm level.  More research is needed to better understand the driving factors behind maize residue management decisions.